Visualization Of Learning English In Elementary Schools - Kiki Pratama Rajagukguk (LPPM STKIP AL MAKSUM, 2020)
The introduction of English to children as early as possible is important. Language learning is a communication skill in variouscommunication contexts. Learning English is essentially learning communication. Therefore, language learning is directed to improvethe learner's ability to communicate, whether oral or written. The most basic and most necessary language elements are: vocabulary,pronunciation, simple grammar, and simple conversation. This introduction can be done by learning, namely by using edutainmentapplications such as multimedia applications for learning English. By combining elements of education and entertainment which are theconcept of edutation and computers as tutorials and demonstrations, so that it can facilitate children's understanding of the materialpresented. . Data collection methods in this study are interviews, observation and literature study. The steps in completing theapplication and research are designing the application draft, making the application, testing, repairing and finally the application finishingprocess. The application developed consists of two compositions, namely learning and training and with the visualization method whichis engineering in images and animation, it is hoped that the children will be more motivated to learn English.